2016
DOI: 10.1109/tnsre.2015.2461495
|View full text |Cite
|
Sign up to set email alerts
|

Adding Real-Time Bayesian Ranks to Error-Related Potential Scores Improves Error Detection and Auto-Correction in a P300 Speller

Abstract: Brain-computer interface (BCI) spellers could improve access to communication for people with profound physical disabilities; however, improved speed and accuracy of these spellers is required to make them practical for everyday use. Here we introduce the combination of P300-speller confidence with the error-related potential (ErrP) to improve online single-trial error detection and correction accuracies in a BCI speller. First, we present a mechanism for obtaining P300-confidence using a real-time Bayesian dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
2
26
0
2
Order By: Relevance
“…Margaux et al [8] and Spuler et al [107] led the work and employed the automatic error correction system (ECS) in their BCI speller. More recently, Zeyl et al [19] employed a two-step row-column speller and reported a 13.67% improvement in selection accuracy for 2.54 symbols/minute with the ECS.…”
Section: B Bci Spellersmentioning
confidence: 99%
See 1 more Smart Citation
“…Margaux et al [8] and Spuler et al [107] led the work and employed the automatic error correction system (ECS) in their BCI speller. More recently, Zeyl et al [19] employed a two-step row-column speller and reported a 13.67% improvement in selection accuracy for 2.54 symbols/minute with the ECS.…”
Section: B Bci Spellersmentioning
confidence: 99%
“…A typical BCI provides an alternative path of communication to a disabled person with the aim of decoding their intention through their neurophysiological signals recorded using EEG [13], [17]. Misclassification of the user's intent results in an erroneous condition which elicits an errorrelated potential (ErrP) signal in the human brain following the perception of the error [18], [19]. The ErrP signal can be integrated with conventional BCIs to form a hybrid-BCI system that can take corrective action on the detection of ErrP to prevent the erroneous action from being executed and ultimately improving the efficacy of the BCI [20]- [22].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al used ICA and Kalman in combination to reduce the interference of white noise on ICA [10] and improve the performance of ICA and ERP extraction; Fukami et al used Particle Filter to extract P300 waveforms [11], and obtained more accurate delay estimation and P300 component amplitude estimation; Ting et al used Kalman filter to extract ERP, by adding the EM algorithm to Kalman filter to achieve a more accurate amplitude estimation [12]; Delaney-Busch et al used Bayesian estimation to study semantic understanding in the process of learning-the trial by trial change of the N400 component in the ERP waveform cannot be achieved by the superimposed average method [13]. Zeyl et al used Bayesian ranks to analyze and calculate the Event related potential scores of each trial, and use event-related potential scores as the time domain features to improve the accuracy of the P300-based speller [14]. This kind of method can handle delay estimation and amplitude estimation on a single-signal frame and improve the classification accuracy.…”
Section: Common Eeg Feature Extraction Methods For Erp Classificationmentioning
confidence: 99%
“…We kept the higher cut-off at 6 Hz to remove any overlapping of the motor imagery signals with our signal of interest. ErrP signals are dominant in the range of [0.1, 10] Hz [10] while motor imagery signals are dominant in the range of [8,12] Hz [40]. As the online experiment is based on motor imagery control, some overlap between motor imagery and ErrP waveforms were found in electrode Cz during preliminary analysis.…”
Section: Filtering and Processing Of Eeg Signalsmentioning
confidence: 98%